Coupled ablation and thermal behavior of an all-composite structurally integrated thermal protection system: Fabrication and modeling. (1st November 2020) - Shi, Shengbo; Wang, Yifan; Yan, Li; Sun, Peijie; Li, Maoyuan; Tang, Shuo
Highlights: A weight-efficient, robust and reliable composite ITPS was designed and fabricated. An analytical model was developed to study the coupled ablation and thermal response. Effects of pyrolysis and thermochemical ablation were considered in the model. The sandwich panels can maintain the back surface temperature within a lower value. ITPS effectively protects any payload exposed to heat flux of 300–500 kW/m 2 for 120 s. Abstract: Structurally integrated thermal protection system (ITPS) was investigated, which has both load-carrying and thermal protection capacities. A novel all-composite sandwich panel with corrugated core was fabricated using the hot press molding method. According to the surface ablation and transient heat transfer theory, an approximate analytical model for predicting the coupled ablation and thermal response was presented for the composite sandwich panel. The effects of pyrolysis reactions, phase transitions, evaporation of quartz fibers, generation of decomposition gases, as well as surface ablation were considered in the mathematical model. After the heat conduction equations had been rewritten by separation of variables and further homogenized by a linearized approach, the governing differential equations were solved using Helmholtz formula and orthogonal expansion technique. A thermal exposure experimental test was performed to validate the approximate analytical model. The monitored temperature–time profiles in the thickness direction are in good agreement with the simulated results. The developed all-composite ITPS successfully protects any payload from an exposure to heat fluxes in the 300–500 kW/m 2 range during approximately 2 min.